www.montereyinstitute.org/courses/DevelopmentalMath/COURSE_TEXT2_RESOURCE/U13_L1_T2_text_final.html

Graph a linear **equation** using **x**- and **y**- intercepts. · Determine ... You **can** think of
a line, **then**, as a collection of an infinite number of individual points that share the
same ... **x** values. **2x** + 3. **y** values. **0**. 2(**0**) + 3. 3. 1. 2(1) + 3. **5**. 2. 2(2) + 3. 7. 3.

jwilson.coe.uga.edu/EMT668/EMAT6680.Folders/Barron/unit/Lesson%205/5.html

Specifically, we graphed the two **equations y** = **2x** + **5** and **y** = (-3/2)x + 2, and ...
Now, we **can** set the right hand side of each **equation equal** to each other
because they both **equal y**. ... x = 5y in the second **equation**, **then** x must also
**equal** 5y in the first **equation**. .... Also, the point (0, 19/14) works, where **x** = **0** and
**y** = 19/14.

www.khanacademy.org/math/cc-eighth-grade-math/cc-8th-systems-topic/cc-8th-systems-with-substitution/v/substitution-method-2

Learn to solve the system of **equations y** = -5x + 8 and 10x + 2y = -2 using
substitution. ... Systems of **equations** with substitution: -3x-4y=-2 & **y**=**2x**-**5** .... =>z
=-**5**. Plug that value in to solve for **X** and you get: =>**x**=12(-**5**) Simplify: .... After you
**do** so, you **will** find the B. **Then** substitute B in the first **equation** to find a ..... -**x** + **y**
+ z = **0**

www.themathpage.com/alg/equation-of-a-line-2.htm

Example 1. Calculate the value of **x** when **y** = **0**, that is, find the **x**-intercept of **y** =
**2x** + 10. Solution. On putting **y** = **0**, we have to solve the **equation**,. 2x + 10, = **0**.
We have: 2x, = −10. **x**, = −**5**. ... a) When we have the **equation** of a straight line,
how **do** we find the ... the same. Find the intercepts by putting **x** -- **then y** -- **equal**
to **0**.

www.analyzemath.com/math_questions/math_questions_2_sol.html

Solution **y** = Log(**x**) if and only if **x** = 10 ^{y}. Interchange **x** and **y y** = 10 ^{x}. Hence f ^{-1}(
**x**) = 10 ... **equal** to 2. Hence their exponents has also to be **equal** 3x - 1 = 4. Solve
for **x x** = **5**/3 ... The quadratic **equation** whose roots are at **x** = 3 and **x** = **5** is given
by .... If Pi < **x** < 3 Pi/2, **then** sin(**x**) **can** be expressed in terms of tan(**x**) as follows

www.varsitytutors.com/sat_math-help/how-to-find-the-solution-for-a-system-of-equations

7x + **y** = 25 – 6x + **y** = 23: 7x – 6x = **x**; **y** – **y** = **0**; 25 – 23 = 2 ... Consider the three
lines given by the following **equations**: **x** + 2y = 1. **y** = **2x** + 3 ... We **can** solve the
system of **equations** by substituting the value of **y** from the second **equation** into ...
If 8x – 9 is 10 less **than 5**, what is the value of 4x? ... The two quantities are **equal**.

www.varsitytutors.com/act_math-help/how-to-find-a-solution-set

We need to find two numbers that **will** mutiply to give us -6. ... If we set one
variable to the other we would get **y** = (**2x** – 7)/3 or x = (3y + 7)/2, but ... If **y** = -7/3,
**then x** = **0**. ... When you multiply a number by **5** and **then** subtract 23, the result is
the same as ... You set up the **equation** 5x – 23 = 3x + 3, **then** solve for x, giving
you 13.

www.rasmus.is/uk/t/F/Su52k03.htm

How **do** we set about finding the points in which two graphs **y** = f(x) and **y** = g(x)
intersect? ... We calculate it by solving the **equation** f(**x**) = **0** . ... Solve the **equation**
x^{2} − **2x** − 3 = **2x** − 3 first graphically, **then** algebraically. ... Example **5** ... definition
of a logarithm we **can** see that x = 1 makes both sides of the **equation equal** to 0 ...

www.wyzant.com/resources/lessons/math/algebra/inequalities

Solving inequalities is not so different from solving regular **equations**. ... means
that the value of the expression on the left must be less **than** or **equal** to 25 ... Try
substituting different values of **x** into the expression -3 - **2x** < **5** and no matter what
value you choose, ... And thus the solution to **x**^2 - 4x - 12 < **0 can** be given as:.